2009
DOI: 10.1371/journal.pone.0007384
|View full text |Cite
|
Sign up to set email alerts
|

The Replicase Gene of Avian Coronavirus Infectious Bronchitis Virus Is a Determinant of Pathogenicity

Abstract: We have previously demonstrated that the replacement of the S gene from an avirulent strain (Beaudette) of infectious bronchitis virus (IBV) with an S gene from a virulent strain (M41) resulted in a recombinant virus (BeauR-M41(S)) with the in vitro cell tropism of the virulent virus but that was still avirulent. In order to investigate whether any of the other structural or accessory genes played a role in pathogenicity we have now replaced these from the Beaudette strain with those from M41. The recombinant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
126
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(141 citation statements)
references
References 44 publications
11
126
1
Order By: Relevance
“…2,27 The S protein is located at the exterior surface of the envelope of IBV and is cleaved into S1 and S2 subunits during maturation. 1 Because the epitopes eliciting neutralizing antibodies are widely distributed within the S protein sequence, as little as 2% variation in amino acid sequence, either by mutation or recombination, can lead to a new IBV serotype. 3,16 Importantly, 2 exclusively Taiwan groups of IBV, Taiwan group I (TW-I) and Taiwan group II (TW-II), have been shown to co-circulate with the vaccine strains in the field.…”
Section: Introductionmentioning
confidence: 99%
“…2,27 The S protein is located at the exterior surface of the envelope of IBV and is cleaved into S1 and S2 subunits during maturation. 1 Because the epitopes eliciting neutralizing antibodies are widely distributed within the S protein sequence, as little as 2% variation in amino acid sequence, either by mutation or recombination, can lead to a new IBV serotype. 3,16 Importantly, 2 exclusively Taiwan groups of IBV, Taiwan group I (TW-I) and Taiwan group II (TW-II), have been shown to co-circulate with the vaccine strains in the field.…”
Section: Introductionmentioning
confidence: 99%
“…As the S1 gene encodes the section of the spike glycoprotein that is responsible for binding to the host cell receptor (Cavanagh et al, 1986), changes to the S1 gene can have significant implications for virulence, tissue tropism and persistence in a host (Wentworth & Holmes, 2007). However, one should also note that investigation into the non-structural genes located in the RdRP region upstream of the S1 gene has concluded that genes in this region also contribute to strain virulence (Armesto et al, 2009). Sequence analysis of the N1/08 RdRP genes and comparative evaluation of the pathogenicity of N1/08 with that of the subgroup 2 and 3 viruses were not possible in this investigation, and would be required to confirm any conclusions as to the implications that these sequence variations have on the virulence of N1/08.…”
Section: Discussionmentioning
confidence: 99%
“…However, such conclusions should be drawn with caution, as the results of this and other studies found no identical substitutions, insertions, or deletions in S proteins between different pathogenic IBV strains and their embryo-passaged, attenuated derivatives, even though the attenuated IBV strains showed distinctly different biological features, including lack of pathogenicity to 1-day-old SPF chicks compared to the pathogenic parental strains [26,30,31] . Some findings suggested that the replicase gene, rather than the S1 or S gene, may be responsible for viral pathogenicity [32,33] .…”
Section: Discussionmentioning
confidence: 99%
“…The ectodomain region [33] and two heptad repeat regions [34] of subunit S2 are involved in oligomerization of the S protein and required for entry into susceptible cells [35][36][37] . Changes in the S2 gene may affect viral entry [32] . In this study, multiple changes in the S2 gene occurred during passage of CK/CH/LDL/97I in embryonated eggs, which may have had an effect on viral entry into chicken host cells in vivo, indirectly decreasing the replication capacity.…”
Section: Discussionmentioning
confidence: 99%